Cutaneous ulceration in Crohn's disease. Issue 1 (January 1970) - Mountain, J. C.
Abstract : This paper describes in detail seven cases of extensive perineal ulceration seen in 207 cases of Crohn's disease at St Mark's Hospital in the last eight years. Four of these cases also had cutaneous ulceration elsewhere. Suggestions are made for the management of further cases of this rare condition.